THE CONCEPT OF ISLAMIC STATEHOOD IN THE THOUGHT OF MUHAMMAD ASAD - Annisa Zalsabillah; Andi Rezal Juhari (Jurnal Al Tasyri'iyyah, 2024)
ABSTRACT This research explores Muhammad Asad's concept of the state and constitutional system, as well as the relationship between religion and the state according to his perspective. Using a library research method with normative Shari'a, socio-historical, and socio-legal approaches, the study draws on primary sources, including Muhammad Asad's writings, and secondary literature on constitutional studies and his ideas. The findings reveal that Muhammad Asad's concept of the state emphasizes governance grounded in the Qur'an, Hadith, and Ijtihad, envisioning an ideal Islamic state with a presidential system. He argues that religion and the state are inseparable, functioning as a support system to reinforce a morality-based governance structure. The study implies that governments should operate on principles rooted in morality. Keywords: Thought; Constitutional System; Muhammad Asad; Siyasah Shari'yyah.